Pengaruh Motivasi Kerja, Lingkungan Kerja Dan Upah Terhadap Produktivitas Kerja Karyawan Pada Sentra Industri Shuttlecock Desa Sumengko Kecamatan Sukomoro Kabupaten Nganjuk - Dwi Ratih Wahyu Andini; Muhammad Mansur; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThe phenomenon that occurs at this time work motivation, work environment and wages become the main topics in the world of work because it is able to make a major contribution to the performance and even employee productivity so as to minimize existing unemployment. This research was conducted at the Shuttlecock Industrial Center in Sumengko Village, Sukomoro Subdistrict, Nganjuk Regency with the aim of analyzing the influence of work motivation, work environment and wages on employee productivity partially or simultaneously, the variables used were work motivation, work environment and wages as independent variables, while productivity employee work as the dependent variable. The sample used was employees in each place of work at the Shuttlecock Industrial Center in Sumengko Village, Sukomoro Subdistrict, Nganjuk District, with 60 respondents using a survey method. The method used is a questionnaire. The analytical tool used is test instrument, classic assumption test, normality test, multiple linear regression test, hypothesis test and coefficient of determination test with the help of SPSS 14.0 software. The results showed that Work Motivation (X1), Work Environment (X2) and Wages (X3) had a joint (simultaneous) effect on Employee Productivity (Y) at the Shuttlecock Industrial Center in Sumengko Village, Sukomoro District, Nganjuk Regency. Keywords: Work Motivation, Work Environment, Wages And Employee Productivity